Estimation of efficiency of band scramblers used for speech information security in narrow-band communication systems - Kukush, V.; Verchyk, D. (Radiotekhnika, 2017)
The advantages of using scramblers in narrow-band voice communication systems are considered and a detailed analysis of strength to hacking of communication channels secured by frequency-domain scrambling technique is given. The effect of the number and order of permutation of the bands on the residual legibility of the scrambled signal is investigated. A description is also given of the developed algorithm for digital signal processing, which realizes the function of the band scrambler in the frequency domain and does not require synchronization between the scrambler and the descrambler.